THE PHENOMENON OF POLYGAMY OF CIVIL SERVANTS (PNS) IN AL MAQASHID AL SHARIA PERSPECTIVE: ANALYSIS STUDY OF GOVERNMENT REGULATION NO 45 OF 1990 IN KONAWE SOUTHEAST SULAWESI - Ipandang Ipandang (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam Negeri Metro, 2021)
This article described the constitutional prohibition for female Civil Servants (PNS) to get marry polygamically which is contained in the Government Regulation No 45 of 1990 in terms of the objectives of Islamic law (Al-Maqashid Al-Syariah). Civil servants as the subjects of this research are the civil servants in Konawe, Southeast Sulawesi. Based on the research focus, the research question was how was Al-Maqasid Al-Syariah on the implementation of Government Regulation No 45 of 1990 regarding the prohibition for female civil servants to become a second wife or more in Konawe? This research used a qualitative approach, while the data collection techniques used in-depth interviews, participatory observation, and documentation. This research found that from the perspective of Al-Maqashid Al-Syariah female civil servants in Konawe, Southeast Sulawesi including their children tend to experience disadvantages. The preservation of religion, soul, mind, property, and offspring will not be fully maintained and fulfilled. It means that the harm of a polygamous family is more significant than its benefit. Therefore, female civil servants are more likely to build polygamous families when they are forced to.